Digital Competence and Attitude Towards ICT Adoption among Business Education Student-Teachers in South-West Nigerian Colleges of Education: A Correlational Study - Olafare Festus Oladimeji (Sagamedia Teknologi Nusantara, 2026)
This study examined the relationship between digital competence and attitude towards information and communication technology (ICT) adoption among Business Education student-teachers in South-West Nigerian colleges of education. The integration of ICT into teaching depends on the competence and disposition of prospective teachers, yet the association between these constructs has rarely been quantified for Business Education in low-resource settings. Anchored in the technology acceptance model and social cognitive theory, the study adopted a correlational survey design. A sample of 149 student-teachers completed a structured questionnaire measuring digital competence, attitude towards ICT adoption and general attitude towards ICT, with Cronbach alpha coefficients of .84, .80 and .85 respectively. Data were analysed using descriptive statistics, Pearson product-moment correlation and multiple linear regression. The respondents reported moderate levels of competence and moderately positive attitudes. Digital competence was significantly and positively related to attitude towards adoption and to general attitude towards ICT, while the two attitudinal facets were strongly associated. Competence and general attitude jointly accounted for 36.1% of the variance in attitude towards adoption, although competence ceased to be a unique predictor once attitude was controlled. The study concluded that attitudinal disposition, rather than competence alone, was the more proximal correlate of adoption, and it recommended that teacher preparation integrate competence building with attention to attitude.